Antioxidant Effects of Sesamol Released from Polymeric Films on Lipid Oxidation in Linoleic Acid and Oat Cereal. (13th March 2012) - Zhu, Xuntao; Schaich, Karen; Chen, Xi; Yam, Kit
<x xml:space="preserve">Abstract</x> The antioxidant effects of sesamol films were evaluated using a food simulant (linoleic acid) and a real food (oat cereal). Sesamol was melt blended with high density polyethylene, linear low density polyethylene and ethylene‐vinyl acetate resins using co‐extrusion to produce sesamol films of multilayer structure; for comparison, films containing butylated hydroxytoluene (BHT) or no additive (as control) were also produced. At least 60% of the initial amount of sesamol remained in the films after extrusion. The release of sesamol from the sesamol films was about six times faster at 30°C than at 10°C. The antioxidant effectiveness of sesamol and BHT was evaluated on the basis of induction period of lipid oxidation, conjugated dienes (for linoleic acid), hexanal (for oat breakfast) and sensory evaluation. Compared with the control film, the sesamol films extended the induction period of linoleic acid by five and eight times at 40°C and 23°C, respectively. After 12 month storage at 23°C, hexanal formation was 59% less in cereal packaged with sesamol films than that packaged with control film. Rancid odours were detected in cereal packaged with control films, but not with sesamol or BHT films. The incorporation of sesamol had only slight effects on tensile properties and transparency. Copyright © 2012 John Wiley & Sons, Ltd.